Comparative Evaluation of Sawdust with Different Casing Materials for the Production of Agaricus bisporus (Lange) Imbach under Natural Bamboo Hut Conditions - Saini, Manisha; Jarial, R. S.; Jarial, Kumud (International Journal of Bio-resource and Stress Management, 2021)
Studies were conducted to evaluate leached sawdust as a casing substrate for the cultivation of Agaricus bisporus either alone or in combination with other substrates at College of Horticulture and Forestry, Neri, Hamirpur, Himachal Pradesh, India during the year 2018–2020. Out of seven casing media evaluated alone, coconut coir pith performed best in terms of all production parameters like time for spawn run (20.3 days) and pinning (15.7 days), sporocarps’ number (55.33), yield (0.679 kg 5 kg-1 compost) and biological efficiency (33.95%). The efficiency of sawdust- leached improved with the addition of other casing substrates. In commercial trial, combination of sawdust - leached with coconut coir pith, spent compost and farmyard manure (1:1v/v) performed better as compared to control (FYM+local soil), but a combination of sawdust- leached+coconut coir pith (1:1v/v) proved to be the best in terms of sporocarps’ number (88.00) and yield (1.271 kg 10 kg-1 compost) despite of the delay in time for spawn run (26 days) and pinning (24.3 days). Casing media also affected the biological efficiency of compost which varied from 10.50% in local soil to 34.05% in sawdust- leached+farmyard manure (1:1v/v) in different experiments. Cap diameter was recorded to be maximum (41.37 mm) in 2 years old spent compost and minimum (34. 27 mm) in sawdust- leached while, stipe length ranged from 14.17 mm in vermicompost-leached to 22.90 mm in sawdust- leached+farmyard manure (1:1v/v). However, fruit bodies harvested from all the casing treatments including standard check were found to be silky smooth and firm to compact.